2000
DOI: 10.1590/s0004-282x2000000500014
|View full text |Cite
|
Sign up to set email alerts
|

Neurocisticercose: estudo clínico e patológico de 27 casos de necrópsia

Abstract: Neurocysticercosis is the most frequent and widespread neuroparasitosis of the human being. The development of brain and leptomeningeal lesions, with subsequent symptoms, are mainly related with the immune status of the host, and to the number and evolutional phase of the parasites. We present the pathological findings in 27 necropsies of patients with neurocysticercosis, which accounted for 3.1% of the necropsies. 77% of the patients were male and the age ranged from 18 to 85 years. In 26% there was previous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
1
4
0
4
Order By: Relevance
“…In a review of 901 autopsies conducted in a department of pathology and anatomy at the University Hospital of Paraná, Brazil, the authors reported on 28 cases of NCC, with medical charts available for 27 of the cases [16]. Of those, 13 were asymptomatic, nine had seizures as a complicating factor of the clinical picture prior to death, four had increased intracranial pressure, one had meningitis, one had a cerebrovascular form and one had dementia noted at some point during the course of the disease.…”
Section: Resultsmentioning
confidence: 99%
“…In a review of 901 autopsies conducted in a department of pathology and anatomy at the University Hospital of Paraná, Brazil, the authors reported on 28 cases of NCC, with medical charts available for 27 of the cases [16]. Of those, 13 were asymptomatic, nine had seizures as a complicating factor of the clinical picture prior to death, four had increased intracranial pressure, one had meningitis, one had a cerebrovascular form and one had dementia noted at some point during the course of the disease.…”
Section: Resultsmentioning
confidence: 99%
“…Nas crianças, a NCC foi considerada pouco frequente (1,5-10%; Md= 5%), comprometendo mais a faixa entre 6-9 anos de idade 1,12,14,15 . Sexo: no geral, a NCC comprometeu mais o sexo masculino (51-80%; Md= 63%) 1,[9][10][11]13,16 . Entretanto, houve envolvimento mais frequente do sexo feminino (53-75%; Md= 73%) naqueles pacientes que apresentaram manifestações graves 1,[17][18][19][20] .…”
Section: Resultsunclassified
“…A letalidade da NCC oscilou de 4,8-25,9% (Md= 14,7%). Esta neuroparasitose foi considerada a causa primária do óbito em 16-34% (Md= 27%) dos estudos de necrópsias, sendo a hipertensão intracraniana (47-69%) resultante do edema cerebral e/ou hidrocefalia hipertensiva fator determinante da morte 1,9,10 . NCC assintomática: a NCC foi considerada como forma assintomática, ou "silenciosa", em necropsias (48-55%; Md= 50%) e em estudos clínicos (1,9-6%; Md= 3,3%) independentemente da forma de apresentação do parasita, fase do desenvolvimento e nú-mero no SNC 1,9,10,21 .…”
Section: Resultsunclassified
See 2 more Smart Citations